Influence of Hemicell® Addition on Diets Containing Different Levels of Crude Fiber on Performance of Laying Hens - Muhammad Ridla; Annisa Imran; Anuraga Jayanegara; Widya Hermana; Allaily Tarman (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
This study was conducted to examine the effect of Hemicell® addition on diets containing different levels of crude fiber on performance and egg quality of laying hens. A total of 72 laying hens aged 21 weeks were randomly divided into 18 experimental units. A completely randomized design with factorial design 2×3 and 3 replications was employed in this study. Factor A was crude fiber level (5% and 8%) and factor B was the level of Hemicell®(0, 100x103 and 200x103 IU/kg ration). Results showed that crude fiber significantly (P<0.01) increased feed consumption and decreased the performance of laying hens. The addition of Hemicell®in diets significantly (P<0.01) decreased feed consumption and increased the performance of laying hens. Hemicell®addition (100 IU) to a diet containing 8% crude fiber significantly (P<0.05) affected egg mass, feed conversion ratio, egg yolk score and egg weight. It can be concluded that diet with 8% crude fiber added with Hemicell® (100 IU) could increase egg mass, feed conversion ratio, egg weight and yolk color score.